Betel Nut Chewing Associated With Severe Periodontitis (Health Renaissance, 2015)
Betel quid chewing has been in practice among people in many Asian countries since ages. It is the most widely used psychoactive substance and an important environmental risk factor for development of oral premalignant lesions and cancer. Arecoline, the major alkaloid of areca nut, has been known to cause cytotoxicity and genotoxicity in mammalian cells in vivo and in vitro and even contributes to carcinogenicity. It also increases the risk and severity of periodontal disease. This paper presents a case of betel nut chewing associated with severe periodontitis in a 32 year old male patient.DOI: http://dx.doi.org/10.3126/hren.v12i1.11990Health Renaissance 2014;12(1):57-60